PENINGKATAN PRESTASI BELAJAR MATA DIKLAT PENGUJIAN BAHAN BANGUNAN MELALUI PEMBELAJARAN MODEL PAKEMSISWA KELAS XI TEKNIK KONSTRUKSI BATU DAN BETON SMKN 7 SEMARANG - Sutiyono, Sutiyono (Universitas Negeri Semarang, 2012)
Implementation of a learning activity in the education eye Testing of building materials and land (PBBT), Engineering Constructions of stone and concrete results and the response was achieved relatively less satisfactory Training participants. Based on the results of the evaluation of the learning activity report, showing the results of the Training participants dicapa an average of under 75 percent. Based on the results of observation and interviews with some of the students, obtained the conclusion that one of the causes of the low achievement of Training value, Training participants when PBBT are following learning, looks much less showed his full attention, because is sleepy and chatting.Work done in improving the outcome of learning students students between learning media tool likes, CD, LCD, modules and application of model PAKEM (active learning, creative, effective and fun) are expected to contribute significantly to improved learning achievement Training participants. As for the application of model learning outcomes with the value of the total percentage of PAKEM reached 80,1189% for aspects of PAKEM cycle 1 and 86,2500% in Cycle 2. Whereas for each of the aspects of PAKEM (Cycles 1 & amp; 2) indicated the following Active (77,38%, 81,49%), creative (79,28%, 84,87%), Effective (81,19%, 87,85%) and fun (82,67%, 89,76%).